Repercussions of Rural to Urban Migration on Male Senior Citizens in Punjab, Pakistan: A Phenomenological Analysis - Beenish Ijaz Butt; Uzma Ashiq; Mohammad Meesam (ASIAN Journal of International Peace & Security (AJIPS), 2021)
National and international migration of youth is a persistent phenomenon that appears as a quest for economic and social development. But when the senior citizens of the family accompany migration, it takes a new dimension that increases their problems. Rural to urban migration as internal migration is a historical tradition of Pakistan but can affect male senior citizens of the family. By finding the said phenomenon as gap in the literature review, this article aims to examine the socio-cultural repercussions of rural-urban migration on male senior citizens in Punjab. Under multi stage sampling, firstly, three districts of Punjab, namely Multan, Lahore, and Rawalpindi were selected purposively; secondly, male senior citizens were interviewed by using volunteer sampling technique. The respondents included the aged male migrants who had migrated in the urban area only before one or less than one year and belonged to the age group of 65 to 74. Respondents were contacted and approached at public places like public parks, restaurants, and hospitals. For data collection, a structured interview guide was developed, which was based on Creswell’s model of data collection for qualitative research and constructed central question, sub-questions and core questions for collecting the data until data was saturated after interviewing 27 respondents. Finally, significant themes were derived to be presented as a result and discussion. “I am in a new world, identity crisis and cultural variation and cultural pluralism” emerged as major themes. It was concluded that government is least interested in dealing with the problems of senior citizens whether they are in rural areas or urban areas. There is no social policy for senior citizens that deal with their problem identification and their solution. In this scenario, migration increases their problems regarding cultural variation and identity crisis. So it is recommended that government might address the issues generated as a result of internal migration and also address the problems of senior citizens through the promulgation of social policies in the province.